Komunikasi Politik: Definisi dan Konsep - Dama Kania Harahap; Ummu Zainab Napitupulu; Rapi Lamnur Siregar; Siti Fatimah Hasibuan; Sampurna, Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In a modern era filled with information upheavals and complex political dynamics, a profound understanding of political communication becomes increasingly crucial. This article outlines a brief introduction to the significance of political communication in shaping public opinion and political decisions. Its aim is to delve into the fundamental concepts and implications of political communication in contemporary society. Descriptive qualitative methods are employed to explore and analyze relevant literature and research. The research findings indicate that political communication plays a central role in shaping the political dynamics of a nation, while a deep understanding of political concepts helps address complex challenges in the political process. The conclusion emphasizes the importance of conducting effective political communication and possessing a strong grasp of political concepts to strengthen democracy and build public trust in the future.